Developing and testing measures of reproductive decision-making agency in Nepal - Laura Hinson; Jeffrey Edmeades; Lydia Murithi; Mahesh Puri (Elsevier, 2019)
Conceptual ambiguity in how we define reproductive empowerment has left the field with inconclusive evidence of its relationship to key reproductive outcomes. Our study aimed to develop and test a measure of reproductive decision-making agency, which is a critical component of reproductive empowerment, in a sample of married women from two Nepalese districts. Initial measures were developed based on theory and previous literature. Next, we used cognitive interviewing techniques to explore local meanings of reproductive empowerment and decision making through eight focus group discussions and 24 in-depth interviews. This process resulted in four core questions used to assess decision making across three domains of reproductive behavior: when to have children, whether to use family planning, and which family planning method to use. We combined these questions to develop an overall assessment of decision-making agency. These measures were included in a quantitative survey conducted with 1000 women, split evenly between the two districts. The combined measure of overall reproductive decision-making agency was internally consistent across the three domains examined (Cronbach's alpha = 0.6416), performed well across a range of validity assessments, including those aimed at assessing construct and criterion validity, and was predictive of a range of reproductive outcomes, particularly those related to feelings of reproductive control. The results suggest that the measures developed here provide insight into the nuances of joint versus sole decision making beyond those provided by standard measures. With better measures of reproductive agency, we can better design interventions for men and women, to meet their reproductive needs.